Skin-core structure moisture power generation device and preparation method thereof
By designing a moisture power generator with a leather core structure, polyvinyl alcohol and metal inorganic salts are used to enhance moisture absorption performance, and combining thermoplastic polyurethane and conductive fillers to improve the conductivity efficiency, the shortcomings of existing moisture power generators in moisture absorption performance and current output are solved, and a more efficient power generation and simplified preparation process is achieved.
Patent Information
- Application Number
- CN202411791290.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
The existing moisture power generation devices have shortcomings in moisture absorption performance and current output power, and it is difficult to meet the demand for stable, convenient and sustainable energy supply.
A moisture power generation device with a skin core structure was designed, using polyvinyl alcohol as the base resin of the cortex, and metal inorganic salts, such as lithium chloride, were added to the cortex to enhance moisture absorption performance. The core layer is selected for thermoplastic polyurethane and conductive fillers, such as multi-wall carbon nanotubes, to ensure conductivity efficiency. The conductive wire does not come into direct contact with the core layer, and the wire is wound through the periphery of the leather for installation.
It improves the moisture absorption performance and current output power of the moisture power generation device, can generate a short-circuit current of about 50μA, simplifies the preparation process of subsequent devices, and is suitable for flexible wearable devices and self-powered power supplies.
Smart Images

Figure CN119602630A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power generation devices, and in particular to a skin-core structured wet gas power generation device and a preparation method thereof. Background Art
[0002] Since the beginning of the 21st century, the coordinated development of energy and electronic technology has brought new development opportunities for new functional fibers. With the popularization of Internet of Things technology and people's pursuit of convenient and environmentally friendly energy utilization methods, the demand for functional fibers that can obtain energy from the environment and apply them to electronic devices has become increasingly prominent. Moisture power generation fibers have emerged as a new type of functional fiber with great potential. In the field of electronic equipment and smart textiles, the demand for self-powered systems is increasing. From wearable health monitoring devices in daily life, to sensor networks in industrial environments, to special equipment in the field of national defense and military industry, they all desire a stable, convenient and sustainable energy supply method. As a ubiquitous resource, moisture has attracted widespread attention for the energy it contains. Moisture generators can use moisture in the environment to generate electricity to power these devices, and have great application value. Summary of the invention
[0003] In view of the problems in the prior art, the present invention designs a wet gas power generation device with a skin-core structure, which has good dilute moisture absorption performance and forms more hydrated ions. These hydrated ions move under the action of the electric field, thereby generating more current and improving the output power of the power generation device. At the same time, different polymer carriers are selected for the skin layer and the core layer, and part of the skin layer can be removed by using the solubility difference, which facilitates the installation of the wet gas power generation device into the application device and simplifies the preparation process of the subsequent device.
[0004] In order to achieve the above technical objectives, the present invention provides a wet gas power generation device with a skin-core structure, the device comprising at least a core layer, a skin layer and a metal wire wrapped around the outside of the skin layer; the skin layer comprises polyvinyl alcohol, the core layer comprises thermoplastic polyurethane and conductive filler, and the skin layer is wrapped around the outside of the core layer; the conductive metal wire is not in direct contact with the core layer.
[0005] In some technical solutions of the present invention, the cortex also includes a metal inorganic salt. Further, the mass fraction of the metal inorganic salt in the cortex does not exceed 35%, and can be specifically 0.1%, 1%, 5%, 10%, 15%, 20%, 25%, 28%, 30%, 32%, 33%, 34%, 35%. The metal inorganic salt can release ions after polyvinyl alcohol absorbs moisture, thereby generating current, and the magnitude of the generated current is related to the rate of migration from the surface of the inorganic salt cortex to the skin core.
[0006] In some preferred technical solutions of the present invention, the metal inorganic salt of the cortex is selected from at least one of sodium chloride, lithium chloride, calcium chloride, and magnesium chloride. Preferably, the metal inorganic salt is selected from lithium chloride. Lithium ions are the smallest ions among alkali metals, have a high charge density, and have a strong polarization ability. They can form a strong ion-dipole interaction with water molecules, so that the cortex can obtain better hygroscopicity, and the power generation device can generate a larger short-circuit current.
[0007] In some technical solutions of the present invention, the conductive filler is selected from at least one of graphene and multi-walled carbon nanotubes. Preferably, the conductive filler is selected from multi-walled carbon nanotubes.
[0008] In some technical solutions of the present invention, the mass ratio of the thermoplastic polyurethane to the conductive filler in the core layer is (3.5-4):1. Within this ratio range, the core layer can obtain better conductivity and be used as the positive electrode of the wet gas power generation device. If the conductive filler is further increased, although it is beneficial to the conductivity of the core layer, it will affect the spinnability of the core layer solution.
[0009] In some technical solutions of the present invention, the conductive metal wire is selected from at least one of zinc wire, aluminum wire, copper wire, silver wire and platinum wire. The conductive metal wire serves as the negative electrode of the wet gas power generation device.
[0010] The present invention also provides a method for preparing a wet gas power generation device with a skin-core structure, which comprises at least the following steps:
[0011] Step 1: prepare a mixed solution of DMSO and water, add polyvinyl alcohol powder into the mixed solution, heat and stir until completely dissolved, and keep warm and stand to degas, so as to obtain a cortex spinning solution for use;
[0012] Step 2: Add thermoplastic polyurethane powder to N,N-dimethylformamide (DMF), heat and stir until completely dissolved to obtain a thermoplastic polyurethane solution, add a dispersant and a conductive filler to N,N-dimethylformamide in sequence, disperse them evenly by ultrasonication to obtain a dispersion of the conductive filler, stir and mix the thermoplastic polyurethane solution and the dispersion of the conductive filler at a high speed to prepare a core layer spinning solution.
[0013] Step 3: The skin spinning solution in step 1 and the core spinning solution in step 2 are spun from two needle tubes of a coaxial spinning needle at different extrusion speeds, and after a coagulation bath, nascent fibers are obtained; after drying the nascent fibers, fibers with a skin-core structure are obtained.
[0014] Step 4: Wrap a metal wire around the outer periphery of the cortex at a predetermined interval to prepare the moisture power generation device.
[0015] In some technical solutions of the present invention, in step 1, after the polyvinyl alcohol is completely dissolved, a metal inorganic salt is added, and the metal inorganic salt is selected from at least one of sodium chloride, lithium chloride, calcium chloride, and magnesium chloride. Preferably, the metal inorganic salt is selected from lithium chloride.
[0016] In some technical solutions of the present invention, in step 1, the mass ratio of dimethyl sulfoxide to deionized water is (0.5-2):1. The addition of dimethyl sulfoxide helps dissolve the polyvinyl alcohol particles, but excessive addition will cause the precipitation of inorganic salts. Furthermore, when the mass ratio of dimethyl sulfoxide to deionized water is 2:1, the solubility of both polyvinyl alcohol and inorganic salts can be taken into account.
[0017] In some technical solutions of the present invention, in step 1, the concentration of polyvinyl alcohol in the cortex spinning solution is 13-16%.
[0018] In some technical solutions of the present invention, in step 1, the concentration of the metal inorganic salt in the cortex spinning solution does not exceed 5%.
[0019] In some technical solutions of the present invention, in step 1, the degree of polymerization of polyvinyl alcohol is 1500-1800, the viscosity in the solution is moderate, and the spinning performance and film-forming performance are good.
[0020] In some technical solutions of the present invention, in step 2, the DMF solution of thermoplastic polyurethane has a mass concentration range of 38-42% and a molecular weight of 12-18w. Thermoplastic polyurethane in the molecular weight range has good solubility, the final solution has a moderate viscosity, and the spinning performance is more ideal.
[0021] In some technical solutions of the present invention, the dispersant in step 2 is preferably hexadecyltrimethylammonium bromide.
[0022] Furthermore, the mass fraction of the hexadecyltrimethylammonium bromide in the dispersion prepared in step 2 is 1.8-2.2%.
[0023] In some technical solutions of the present invention, in the core layer spinning solution prepared in step 2, the mass concentration of the thermoplastic polyurethane is 14-18%, and the mass concentration of the conductive filler is 4-4.5%. The core layer spinning solution can have good spinning performance and obtain ideal conductive properties of the core layer.
[0024] In some technical solutions of the present invention, the component of the coagulation bath in step 3 is methanol.
[0025] In some technical solutions of the present invention, in the step 3, when the skin layer and the core layer are coaxially spun, the ratio of the spinning solution extrusion speed is (1-4): 1, specifically 1: 1, 2: 1, 3: 1, 4: 1. The higher the skin layer spinning solution extrusion speed, the thicker the skin layer thickness of the prepared skin-core structure fiber, which can further improve the tensile strength and current intensity of the prepared skin-core fiber. A low skin layer thickness will affect the conductivity of the skin layer, and a high thickness will make spinning more difficult.
[0026] In some technical solutions of the present invention, one end of the skin-core structure fiber obtained in step 4 can be immersed in boiling water for several minutes, and after a part of the skin layer is completely dissolved, it is sealed and dried at room temperature for 45-50 hours, and then a metal wire is wound around the skin layer at a predetermined interval, and the metal wire does not contact the exposed core layer. Through this preparation method, a part of the core layer can be exposed, which is convenient for connecting the electrode to the device.
[0027] The present invention also provides an application of a skin-core structured moisture power generation device, which can be applied to flexible wearable devices and self-powered power supplies.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention uses polyvinyl alcohol as the base resin of the cortex, which has good hygroscopic properties. When the moisture in the environment is absorbed by PVA, the oxygen-containing functional groups dissociate to produce a large number of mobile charged ions, forming an ion concentration gradient. Subsequently, these ions will migrate along the direction of the ion concentration gradient, resulting in a potential difference between the two electrodes, thereby inducing voltage output. Furthermore, adding metal inorganic salts to the cortex can absorb moisture in the air to form hydrates, promote the hygroscopic properties of the cortex, and form a solution to release ions, further increasing the current intensity to a level of about 50μA.
[0030] 2. The core layer of the present invention is made of thermoplastic polyurethane, and the conductive filler can be stably dispersed in the resin, thereby ensuring good conductive efficiency of the core layer. In addition, thermoplastic polyurethane has good water conductivity, and the skin layer can be dissolved by boiling in water to expose the core layer, which is convenient for the power generation device to be connected to the device.
[0031] 3. The present invention can use a wet coaxial spinning preparation method, which is simple and can achieve continuous production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 This is a schematic diagram of a skin-core structure power generation device prepared in an embodiment of the present invention;
[0034] 1. Skin layer; 2. Core layer; 3. Conductive metal wire;
[0035] Figure 2 This is an electron microscope image of the cross section of the skin-core structure power generation device prepared in Example 1 of the present invention;
[0036] Figure 3 Schematic diagram of the process of preparing a skin-core structure power generation device according to the present invention
[0037] Figure 4 This is a tensile strength test diagram of the skin-core structure power generation device prepared in Example 1 and Examples 7-9;
[0038] Figure 5 This is a test diagram of the skin conductivity of the skin-core structure power generation device prepared in Example 1 and Examples 7-9. DETAILED DESCRIPTION
[0039] The following is a clear and complete description of the technical solutions in the present invention in conjunction with the embodiments of the present invention. The described embodiments are part of the embodiments of the present invention, but not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] The materials used in the embodiments of the present invention are all commercially available products, as shown in the following table:
[0041] name Specification Manufacturer Polyvinyl alcohol Degree of polymerization: 1799 Shanghai MacLean Biochemical Technology Co., Ltd. Thermoplastic polyurethane Molecular weight:15w Zhongcheng Plastic Co., Ltd. Multi-walled carbon nanotubes Purity ≥95% Nanjing Xianfeng Nanomaterial Technology Co., Ltd. Cetyltrimethylammonium bromide (CTAB) AR Tianjin Guangfu Fine Chemical Research Institute Sodium chloride AR Xilong Scientific Co., Ltd. Lithium chloride monohydrate AR Shanghai MacLean Biochemical Technology Co., Ltd. Calcium Chloride Anhydrous AR Xilong Scientific Co., Ltd. Magnesium chloride hexahydrate AR Xilong Scientific Co., Ltd. Copper wire 99.9% Anhui Zhengying Technology Co., Ltd.
[0042] Example 1
[0043] Dissolve 5g of lithium chloride in 26.7g of deionized water, then add 53.3g of dimethyl sulfoxide, stir thoroughly and then add 15g of polyvinyl alcohol powder, heat at 95°C and stir at 100rpm until the polyvinyl alcohol powder is completely dissolved, and keep warm and stand to degas, to obtain a polyvinyl alcohol / inorganic salt cortex spinning solution for use;
[0044] 16g of thermoplastic polyurethane powder was added to 24g of N,N-dimethylformamide solution, heated at 95°C and stirred at 100rpm until completely dissolved; 2g of hexadecyltrimethylammonium bromide was weighed and added to 53.8g of N,N-dimethylformamide solution and heated and stirred until the powder was completely dissolved, and then 4.2g of multi-walled carbon nanotubes were added to the solution and ultrasonically dispersed to obtain a multi-walled carbon nanotube dispersion; the polyurethane solution and the multi-walled carbon nanotube dispersion were mixed at a ratio of 2:3 by high-speed stirring, and finally a core spinning solution with a polyurethane mass fraction of 16% and a multi-walled carbon nanotube mass fraction of 4.2% was obtained;
[0045] The prepared skin layer spinning solution and core layer spinning solution were spun from two needle tubes of a coaxial spinning needle at an extrusion speed ratio of 4:1, and then subjected to a methanol coagulation bath to obtain nascent fibers; after drying the nascent fibers, fibers F1 with a skin-core structure were obtained;
[0046] One end of the fiber F1 with a skin-core structure is immersed in boiling water for several minutes, and after the skin layer is dissolved, it is sealed and dried at room temperature for 48 hours, and then a copper wire is wound around the skin layer at a spacing of 2 mm to prepare the wet gas power generation device.
[0047] Compared with Example 1, the only difference between Example 2 and Example 1 is that the metal inorganic salt used in the cortex is sodium chloride.
[0048] Compared with Example 1, the only difference between Example 3 and Example 1 is that the metal inorganic salt used in the cortex is calcium chloride.
[0049] Compared with Example 1, the only difference in Example 4 is that the metal inorganic salt used in the cortex is magnesium chloride.
[0050] Compared with Example 1, the only difference in Example 5 is that the amount of lithium chloride added to the cortex is 2.5 g.
[0051] Compared with Example 1, Example 6 is different in that the skin layer contains only polyvinyl alcohol resin without adding metal inorganic salt.
[0052] Compared with Example 1, Example 7 is different in that the extrusion speed of the core layer spinning solution is kept unchanged, and the skin layer spinning solution and the core layer spinning solution are respectively extruded from the two needle tubes of the coaxial spinning needle head at a ratio of 3:1.
[0053] Compared with Example 1, Example 8 is different only in that the extrusion speed of the core layer spinning solution is kept unchanged, and the skin layer spinning solution and the core layer spinning solution are respectively extruded from two needle tubes of the coaxial spinning needle head at a ratio of 2:1.
[0054] Compared with Example 1, Example 9 is different only in that the extrusion speed of the core layer spinning solution is kept unchanged, and the skin layer spinning solution and the core layer spinning solution are respectively extruded from two needle tubes of the coaxial spinning needle head at a ratio of 1:1.
[0055] Comparative Example: Compared with Example 6, the difference is that the skin layer and the core layer use sodium alginate as the base resin.
[0056] Test experiment:
[0057] 1. Hygroscopicity test: The moisture absorption rate of the sample is tested using an electronic balance. The sample is placed in a constant temperature and humidity environment, and the moisture absorption rate is calculated as the weight after moisture absorption - the weight when dry / the weight when dry. The moisture absorption interval is 2 hours.
[0058] 2. Current and voltage test: All voltage and current signals are recorded in real time using a Keithley 2400 multimeter controlled by a LabView-based data acquisition system. The bias voltage for testing short-circuit current is set to 0mV, and the bias current for testing open-circuit voltage is set to 0nA. To avoid electrostatic interference, all samples were short-circuited before testing.
[0059] 3. Tensile strength test: The strength and elongation of the sample were tested using a universal mechanical testing machine (EZ-LX) from Suzhou Shimadzu Instrument Co., Ltd. The stress-strain curve was used to characterize and calculate the tensile strength. The stretching speed was 50 mm / min and the stretching interval was 30 mm.
[0060] 4. Conductivity test: The diameter of the conductive composite fiber was measured using an electron microscope, and the Keithley DMM75107 of Keithley Co., Ltd. was used at a certain length. 1 / 2 digital multimeter was used to measure the resistance of different samples, and the conductivity of the fiber was calculated by formula (1): σ=1 / ρ(1)σ represents conductivity, ρ represents resistivity.
[0061] Test result description:
[0062] Table 1 Hygroscopicity and current and voltage test results of the embodiments and comparative examples
[0063]
[0064] As shown in Table 1, it can be seen from the water absorption rate, current and voltage tests of Examples 1-9 and the comparative example that when lithium chloride is selected as the metal inorganic salt, the hygroscopic performance of the device is the strongest, and the 2h water absorption rate can reach up to 14.3%, and the corresponding short-circuit current and open-circuit voltage values can reach 52.87μA and 1V; in Example 6 where no inorganic salt is added, the short-circuit current and open-circuit voltage values generated can also reach 2.2μA and 0.22V, which are better than the comparative example, indicating that polyvinyl alcohol has better hygroscopic power generation performance.
[0065] like Figure 3 , Figure 4 As shown, in Example 1 and Examples 7-9, fibers with different skin-core thickness ratios were prepared at different skin-core extrusion speeds. In terms of short-circuit current and open-circuit voltage data, as the skin thickness increases, the conductivity and tensile strength are further improved.
[0066] Finally, a few points should be explained: Although the present invention has been described in detail above with general descriptions and specific embodiments, on the basis of the present invention, the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit it; although the present invention has been described in detail with reference to the aforementioned embodiments, ordinary technicians in this field should understand that: it is still possible to modify the technical solutions recorded in the aforementioned embodiments, or to replace part or all of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solution deviate from the scope of the technical solution of the embodiments of the present invention.
Claims
1. A skin-core structure wet gas power generation device, characterized in that: The device comprises at least a core layer, a skin layer and a conductive metal wire wound around the skin layer; the skin layer comprises polyvinyl alcohol, the core layer comprises thermoplastic polyurethane and conductive filler, the skin layer is wrapped around the core layer; the conductive metal wire is not in direct contact with the core layer.
2. The wet gas power generation device according to claim 1, characterized in that: The cortex also includes a metal inorganic salt; the mass fraction of the metal inorganic salt in the cortex does not exceed 35%; the metal inorganic salt in the cortex is selected from at least one of sodium chloride, lithium chloride, calcium chloride and magnesium chloride.
3. The wet gas power generation device according to claim 1, characterized in that: The mass ratio of the thermoplastic polyurethane to the conductive filler in the core layer is (3.5-4):1; the conductive filler is selected from at least one of graphene and multi-walled carbon nanotubes.
4. The wet gas power generation device according to claim 1, characterized in that: The conductive metal wire is selected from at least one of zinc wire, aluminum wire, copper wire, silver wire and platinum wire.
5. A method for preparing the wet gas power generation device according to claim 1, characterized in that: At least the following steps are included: Step 1: prepare a mixed solution of DMSO and water, add polyvinyl alcohol powder into the mixed solution, heat and stir until completely dissolved, and keep warm and stand to degas, so as to obtain a cortex spinning solution for use; Step 2: Add thermoplastic polyurethane powder to N,N-dimethylformamide (DMF), heat and stir until completely dissolved to obtain a DMF solution of thermoplastic polyurethane; add a dispersant and a conductive filler to N,N-dimethylformamide in sequence, and disperse them evenly by ultrasonication to obtain a dispersion of the conductive filler; stir and mix the DMF solution of thermoplastic polyurethane and the dispersion of the conductive filler at a high speed to prepare a core layer spinning solution. Step 3: The skin spinning solution in step 1 and the core spinning solution in step 2 are spun from two needle tubes of a coaxial spinning needle at different extrusion speeds, and after a coagulation bath, nascent fibers are obtained; after drying the nascent fibers, fibers with a skin-core structure are obtained. Step 4: Wrap a metal wire around the outer periphery of the cortex at a predetermined interval to prepare the moisture power generation device.
6. The preparation method according to claim 6, characterized in that: In the step 1, after the polyvinyl alcohol is completely dissolved, a metal inorganic salt is added, wherein the metal inorganic salt is selected from at least one of sodium chloride, lithium chloride, calcium chloride, and magnesium chloride; and the mass ratio of the dimethyl sulfoxide to deionized water is (0.5-2):
1.
7. The preparation method according to claim 6, characterized in that: In the step 2, the mass concentration of the thermoplastic polyurethane DMF solution is in the range of 38-42% and the molecular weight is 12-18w.
8. The preparation method according to claim 6, characterized in that: In the core layer spinning solution prepared in step 2, the mass concentration of the thermoplastic polyurethane is 14-18%, and the mass concentration of the conductive filler is 4-4.5%.
9. The preparation method according to claim 6, characterized in that: The coagulation bath component in step 3 is methanol; when the skin layer and the core layer are coaxially spun in step 3, the ratio of the spinning solution extrusion speed is (1-4):
1.
10. An application of the wet gas power generation device according to claim 1, characterized in that: The moisture power generation device can be applied to flexible wearable devices or self-powered power sources.
Citation Information
Cited By
Moisture power generation covering yarn and preparation method and application thereof
CN122189907A